Who is the sinner? The view of Karl Barth - Zyl, F. J. van (HTS teologiese studies, 2007)
This article focuses on Karl Barth’s view of the human being as sinner. In accordance with his christological approach to all theological matters, the article aims to argue that Barth describes the image and character of the sinner as mirrored by the obedient suffering and vicarious death of Jesus Christ on the cross in the place of all sinners of all times – past, present and future. According to Barth, the price that God paid in surrendering God’s only Son to such suffering indicates the enormous guilt and existence of every sinner. All human beings are hopelessly in debt and can only be delivered from sin through God’s graceful remission of sin.